MATERIAL CULTURE AS A LIFESTYLE AND SELF-IDENTITY: A CASE STUDY OF THE ROTATING SAVINGS TO BUY AN IPHONE IN INDONESIA - Assilmi, Ghilman (UI Scholars Hub, 2024)
Branding as a cultural production is a phenomenon that involves the creation of narratives, symbols, and identities that affect individuals and social. Through the study of material culture, this article discusses the representation of a person's lifestyle and self-identification in meeting the needs of smartphones with the iPhone brand. Using the literature study method, social media data on the internet shows that there is a business service strategy in the form of savings or social gathering in buying an iPhone to consumers. The research results show that strong branding images built by Apple Inc. make people who economically are not in the upper middle class and cannot pursue these lifestyles (lifestyle and consumption) so that they take actions that can provide middle-class touch which can also be called virtual consumption. In this case, material culture can be understood as a giver of meaning and related, with strength, power, and self -construction.